2015
DOI: 10.1002/joc.4364
|View full text |Cite
|
Sign up to set email alerts
|

Interannual variability of the onset of the South China Sea summer monsoon

Abstract: This article investigates the year-to-year variability of the onset of the South China Sea summer monsoon (SCSSM) and the possible influences exerted by the surface temperature anomalies over land and sea. Early and late monsoon onsets are related to the temperature anomalies in different regions. It is found that an early onset follows negative sea surface temperature (SST) anomalies in the central tropical Pacific (CP) Ocean during the preceding winter and spring, corresponding to a CP La Niña. In contrast, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 60 publications
(95 reference statements)
1
25
0
Order By: Relevance
“…El Niño–Southern Oscillation (ENSO) is one of the major factor affecting the variabilities of Asian monsoons (Huang et al ., ; Yuan and Yang, ; Chen et al ., ). For example, previous studies show that the SCSSM onset tends to occur later (earlier) during El Niño (La Niño) decaying summer (Zhou and Chan, ; Ding et al ., ; Luo et al ., ). Besides the monsoon onset, the monsoon withdrawal is also significant to societies since it signals the termination of the summer rainy season (Luo, ; Stolbova et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…El Niño–Southern Oscillation (ENSO) is one of the major factor affecting the variabilities of Asian monsoons (Huang et al ., ; Yuan and Yang, ; Chen et al ., ). For example, previous studies show that the SCSSM onset tends to occur later (earlier) during El Niño (La Niño) decaying summer (Zhou and Chan, ; Ding et al ., ; Luo et al ., ). Besides the monsoon onset, the monsoon withdrawal is also significant to societies since it signals the termination of the summer rainy season (Luo, ; Stolbova et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…The onset and withdrawal timing of the monsoon season should be correctly determined and predicted. As one important component of the Asian summer monsoon (Tao and Chen, ), the onset of the South China Sea summer monsoon (SCSSM) indicates the end of dry season and beginning of the summer rainy season over East Asia (Wang et al ., ; Ding and Chan, ; Luo et al ., ), whereas its withdrawal indicates the end of the rainy season.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the strength of the EASM and the associated rainfall are subject to the western North Pacific subtropical high (WNPSH) [ Lin and Wang , ]. Therefore, many efforts have been devoted to study the behaviors of WNPSH [ Chan , ; Ling et al ., ] and its possible impacts on Asian climate [e.g., Hong et al ., ; Luo et al ., ; Zhu et al ., ]. The change of WNPSH exerts considerable impacts on the spatiotemporal variations of precipitation in southeastern China [ Wang and Chen , ] and eastern China [ Ding et al ., ; Zhu et al ., ; Lu et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The variability of precipitation over East Asia is considerably modulated by the variation of sea surface temperature (SST). Previous work suggested that El Niño‐Southern Oscillation (ENSO) and Indian Ocean Dipole (IOD) are specifically the dominant causal factors at the interannual scale (Chang et al , ; Wang et al , ; Ding and Chan, ; Luo et al , , ). For instance, an El Niño‐like SST pattern in June 2015 intensified the western Pacific subtropical high and shifted it southwestward, thus increasing the occurrence of heavy precipitation in eastern China (Wang and Gu, ).…”
Section: Introductionmentioning
confidence: 99%